A Critical Review of Tax Audit Quality Factors: A Research Synthesis - Nor Asiah Taib; Izlawanie Muhammad; Suhaila Abdul Hamid (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2025)
Islamic Banking, Accounting & Finance International Conference 2024 (iBAF 2024) Theme: "Revolutionizing Islamic Finance, Accounting and Banking Through Artificial Intelligence (AI)" 12-13 November 2024 Editors: Dr. Amalina Mursidi, Dr Suhaila Abdul Hamid, Prof Madya Dr. Norhaziah Nawai, Prof Madya Dr. Muhamad Azrin Nazri,Dr. Mohd Adha Ibrahim